Mewujudkan Keadilan Distributif (Distributive Justice) Sebagai Upaya dalam Mengatasi Kemangkiran (Abseenteism) Pegawai - Badarwan Badarwan; Syamsuddin Syamsuddin (Shautut Tarbiyah, 2016)
This article was prepared with the aim to assess the steps that can be taken to realize distributive justice as countermeasures for employee absenteeism. Distributive justice in general diandang as perceptions about the fairness perceived by a person based on the ratio of the individual results obtained for his contribution as compared to the ratio of the result of the contributions of others. Employee perceptions is strongly associated with the comparison an employee of the results obtained for the work that has been accomplished with the results obtained other employees who generally had a load and performance are considered equivalent. If the result is obtained after dikomparasikan with others differ primarily considered inferior it will bring the perception of unfair behavior towards leadership. The results of employee perceptions is what can menimbulkann correlations and relationships with other employees work behavior is very important in maintaining the effectiveness and efisiens agencies. One aspect that could be affected is absenteeism. In the sense that if an employee discount perssepsi good against distributive justice better then kemangkirannya level will be low and vice versa pleasan.Key Words: Distributive Justice, Absenteeism